2013
DOI: 10.1007/s10555-013-9418-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor type-specific and skin region-selective metastasis of human cancers: another example of the “seed and soil” hypothesis

Abstract: Metastasis of human cancer is an organ-selective process that is determined by anatomical and biological factors as well as by specific microenvironmental properties. Dissemination of visceral malignancies to the skin is rather rare and usually occurs in a later stage of the disease. Using statistical approaches, both positive (renal and lung cancers) and negative (pancreatic and liver cancers) organ preferences can be identified in a variety of cancers. While certain cancer types are characterized by random d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The reasons why these organs are rarely involved in cancers including NSCLC are as follows. K. A. Kovács, et al [ 15 ] proposed that the skin only shared 5 % of the cardiac output of blood at resting condition, and was a very active part of immune system. The rarity of skeletal muscle metastases has been attributed to changes in pH, metabolite accumulation, variable blood flow, and variation in tissue pressure [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why these organs are rarely involved in cancers including NSCLC are as follows. K. A. Kovács, et al [ 15 ] proposed that the skin only shared 5 % of the cardiac output of blood at resting condition, and was a very active part of immune system. The rarity of skeletal muscle metastases has been attributed to changes in pH, metabolite accumulation, variable blood flow, and variation in tissue pressure [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…patients, was followed by quantitative RT-PCR-based assay to be validated (26). Gastric cancer cells must acquire an aggressive phenotype to form hematogenous metastasis (27,28) and therefore may express molecules with activities that differ from those of cancer cells that invade the peritoneum and lymph nodes. To test this hypothesis, we designed a recurrence pattern-specific transcrip-tome analysis strategy to identify genes that were specifically upregulated in each recurrence pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Most skin metastases occur in regions close to the primary cancer. A number of cancers demonstrate a colonization preference to the region of origin: lung cancer to the supradiaphragmatic (mostly chest) and colorectal cancers to the infradiaphragmatic (abdominal) skin regions [ 19 , 20 ]. It was also found that cancer of the upper lobes of the lungs have a greater tendency to metastasizing in skin [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that cancer of the upper lobes of the lungs have a greater tendency to metastasizing in skin [ 21 , 22 ]. These findings are clinically relevant and useful especially in patients where skin metastasis is the first indication of a malignancy [ 20 ]. Metastasis of human cancer is an organ-selective process that is determined by anatomical and biological factors as well as by specific microenvironmental properties [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation